A diphtheria outbreak in Johor Bahru, Malaysia: Public health investigation and response - Peter Seah Keng Tok; Misbaha Jilani; Nurul Fateha Misnar; Nor Suzila Bidin; Norli Rosli; Haidar Rizal Toha (Journal of Infection in Developing Countries)
Introduction: Diphtheria is an acute infectious disease caused by Corynebacterium diphtheriae. Although the incidence of diphtheria worldwide has rapidly declined following the largely successful diphtheria toxoid-based vaccines, concerns persist for those who were unvaccinated or incompletely vaccinated. In this report, we describe a recent diphtheria outbreak in Malaysia involving four confirmed diphtheria cases.